Mathematical Modeling and Simulation of Enzyme Assisted Bioactive Compound Extraction from Allium Cepa Using Response Surface Methodology - Thirugnanasambandham, K. (Asian Journal of Engineering and Applied Technology, 2018)
In this present study, an attempt was made to investigate the enzyme assisted extraction process to extract the phenolic compounds from onion (Allium cepa) under various operating conditions such as temperature, extraction time and enzyme concentration. Three factors three level Box-Behnken response surface design (BBD) coupled with desired function methodlogy was used to optimize and model the extraction process. Optimum extracting conditions for the maximum phenloic compounds were determined and it was found to be: temperature of 40 0C, extraction time of 16 hour and enzyme concentration of 2 %. Under these conditions, 9.25 % of phenolic compound was extracted. Extracted phenolic compounds can be regarded as the promising antioxidants to scavenge the DPPH free radicals.